Saving on a rainy day, borrowing for a rainy day - Sule Alan; Thomas Crossley; Hamish Low (Institute for Fiscal Studies (IFS), 2012)
The aim of this paper is to understand what a recession means for individual consumers, and to model in a life-cycle framework how individuals respond to recessions. Our focus is on the sharp increase in savings rates that have been observed in the current and recent recessions. We show empirically that these saving spikes were short-lived and common to all working age groups. We then study life-cycle models in which recessions involve one or more of: (i) an aggregate permanent negative shock to individual income; (ii) an increase in the variance of idiosyncratic permanent shocks; (iii) a tightening of credit constraints; (iv) as set market crashes. In simulations and in the data we aggregate explicitly from individual behavior. We model credit tightening as a constraint on new borrowing and this generates an option value of borrowing in good times. We show that the rise in the aggregate savings ratio is driven by increases in uncertainty, rather than tightening of credit; temporary shocks to the supply of credit generate increases in saving only among younger agents.
Keywords: D91; E21; D14; G01; 330; Credit constraints; savings; recessions; uncertainty